The Collaboration Between Art History and Genetics – An Unlikely Marriage of Disciplines - De Smet, Ive; Vergauwen, David (Frontiers in Plant Science, 2021)
Our fruits, vegetables and cereal crops stem from a wild ancestor and have undergone major changes through millennia of domestication and selection. There are various ways to reveal plant diversity over time, and one of these is through the combination of art history and genetics (also known as #ArtGenetics). Here, we discuss this approach from the art historian’s point of view and flag the advantages and caveats of such an approach. We also advocate for the development of an integrated, global art database to facilitate such analyses.